KURIKULUM PROTOTYPE DAN MODEL PjBL DALAM PERSPEKTIF GURU SMPN 5 KOTA JAMBI - Dudu Mawarida Sembiring Nana Armytha Rustam Priyanto (Jurnal Tunas Pendidikan, 2022)
The prototype curriculum is a new paradigm curriculum that was created to overcome the literacy crisis in Indonesia. The purpose of this curriculum is to restore this status to be better with the concept of student center and the profile of Pancasila. The research was conducted by conducting interviews with teachers in 5 public junior high schools in Jambi. The approach used is a qualitative approach with literature and documentation techniques. Teachers and schools are still implementing the 2013 curriculum and are preparing to implement a prototype curriculum so that the similarities and differences between the two curricula will appear. The interview results were analyzed by adhering to relevant theories and previous research. Furthermore, the authors independently make general conclusions to clarify the intent and purpose of the interview data with existing supporting theories. The conclusion of this study states that the prototype curriculum is seen as a good solution for current education, especially during the pandemic. The 2013 curriculum does not necessarily disappear, but is complemented and refined according to the needs of students and teachers in today's learning (Covid-19 pandemic) by the prototype curriculum. Finally, results/product/work-oriented learning models such as the PjBL Model are considered to be the most suitable for the Prototype Curriculum criteria.